Operation Condor on trial: Justice for transnational human rights crimes in South America - Lessa, F (Cambridge University Press, 2018)
In May 2016, an Argentine federal court concluded a momentous trial, convicting 15 defendants of illegal kidnappings and torture committed against over 100 victims of Operation Condor, and of asociación ilícita (‘illicit association’: conspiracy to commit a criminal offence) to perpetrate these violations. Operation Condor was the codename given to a continent-wide covert operation devised in the 1970s by South American regimes to eliminate hundreds of left-wing activists across the region. The Operation Condor verdict of 2016 broke new ground in human rights and transitional justice, for its innovative focus on transnational crimes and for holding state agents accountable for extraterritorial human rights violations. By analysing this pioneering case, the article brings the question of cross-border crimes into academic debate. As borders become more porous, scholars and practitioners can no longer afford to side-line the topic of accountability for transnational crimes.